2017
DOI: 10.4314/ijbcs.v11i1.10
|View full text |Cite
|
Sign up to set email alerts
|

<i>In vitro</i> and <i>in vivo</i> antiplasmodial activity of extracts from <i>Polyalthia suaveolens, Uvaria angolensis and Monodora tenuifolia</i> (Annonaceae)

Abstract: The present study aimed at investigating the in vitro and in vivo susceptibility of malaria parasites to crude extracts and fractions from Polyalthia suaveolens, Uvaria angolensis, and Monodora tenuifolia. The ethanolic extracts were partitioned using water, dichloromethane, hexane, and methanol. The most promising fraction was subjected to column chromatography. The antiplasmodial effect of extracts, fractions and subfractions against P. falciparum Chloroquine resistant (PfK1) strain was determined using SYBR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The survey showed that the prevalence of malaria cases were more among the female gender than the male. This observation agreed with workers' reports on malaria (Edogun et , 2017;Nas et al, 2017). This increase in prevalence among females that reported for medical advice could be as result of decreased immunity particularly among pregnant women that make them more susceptible to infection (Nas et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The survey showed that the prevalence of malaria cases were more among the female gender than the male. This observation agreed with workers' reports on malaria (Edogun et , 2017;Nas et al, 2017). This increase in prevalence among females that reported for medical advice could be as result of decreased immunity particularly among pregnant women that make them more susceptible to infection (Nas et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Malaria a prevalent tropical disease in sub-Saharan Africa that accounted for the highest global mortality of 584 000 (90%) in 2013 (Mfopa et al, 2017). About 50% of the Nigerian population will have at least one episode of malaria annually while children below the age of five (about 24 million) will have two to four attacks annually (WHO, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…katangensis extracts sufficiently reduced parasitemia in the animals on day 7 of observation (Table 3) and these reductions in parasitemia were dose dependent. This situation is observed in plants with antimalarial activity in the rodent model and constitutes one pledge of their activities [49][50][51]. According to the classification previously proposed [52], all extract presented a good antiplasmodial activity in vivo.…”
Section: Discussionmentioning
confidence: 94%
“…Despite the permanent progress in pharmaceutical companies, resistance to different drug classes (Mfopa et al, 2017;Etou et al, 2019) has become an increasingly important problem (Madhulika et al, 2004, Lakshmi et al, 2006 especially in Subsahelian Africa where the income of ¾ of the total population do not allow them to afford and/or achieve antibiotherapy. In addition, although three vaccines are currently recommended by the WHO to prevent typhoid: an injectable vaccine on the purified Vi antigen (aka ViPS vaccine), the live attenuated oral Ty21a vaccine in the first instance and the latest generation typhoid conjugate vaccine (TCV), there is to date no vaccine against paratyphoid fever (Agwu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%